2015
DOI: 10.1177/2010105815610137
|View full text |Cite
|
Sign up to set email alerts
|

Is simultaneous pancreas kidney transplant the most cost-effective strategy for type 1 diabetes patients with renal failure?

Abstract: Introduction: Simultaneous pancreas kidney transplant (SPK) has shown beneficial outcomes in type 1 diabetes patients with renal failure (IDDM-RF). The objective of this study was to assess its cost-effectiveness compared with other treatment strategies for IDDM-RF. Methods: A decision analytic model was developed for IDDM-RF treatment with four possible strategies: deceased donor kidney transplant (DDKT), living donor kidney transplant (LDKT), SPK and dialysis. A cost-utility analysis from the healthcare prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Douzdijan et al . [6] found SPK transplantation yielded the best gains in QALY at five years (2.36), compared to deceased donor kidney alone transplantation (1.38) and dialysis (0.68) [24]. This has been corroborated by more recent data.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Douzdijan et al . [6] found SPK transplantation yielded the best gains in QALY at five years (2.36), compared to deceased donor kidney alone transplantation (1.38) and dialysis (0.68) [24]. This has been corroborated by more recent data.…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, using registry data from Singapore and the United States, Ong et al . [24] also found that SPK transplantation yielded the best QALY at five years (3.03), compared to deceased donor kidney alone transplantation (2.08) and dialysis (0.64). While the previous studies demonstrate the survival advantages of SPK transplantation over deceased donor kidney transplantation and dialysis, the present study also accounts for recipient age interactions and uses a probabilistic rather than a deterministic approach to determine the incremental benefits in life years and quality‐adjusted LYS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations